THE IMPLEMENTATION OF GENRE-BASED APPROACH IN THE TEACHING OF ENGLISH AT SMP NEGERI 5 SRAGEN - Chayati, Umi Nur (2009)
The objective of the research is to describe the implementation of Genre-Based Approach (GBA) in the teaching of English. Besides, it was also conducted to study the procedures of the process of teaching English using genre-based approach, the activities used in teaching English applying genre-based approach, the problems in implementing of GBA, and the way used by the teachers to overcome the problem in implementing the GBA in the process of teaching English. The data of this research are information taken from several techniques including non-participant observation, in-depth interviewing, and document analysis. In analyzing the data, the researcher conducted reducing the data, displaying the data, concluding and verifying. The results compiled from the implementation collected shows as follows: firstly, the application of GBA which is viewed from six dimensions which appear from the research, the objectives, the model of syllabus, the function of genre-based in teaching and learning activities, students and teachers roles in the teaching and learning activities. Secondly, the procedure in the teaching and learning using GBA is taking three steps: opening, implementation, and closing. Thirdly, the activities of teaching English are using curriculum cycle: BKOF, MOT, JCOT, and ICOT. Fourthly, this research also shows that although this approach has good influence to development the teachers and the students’ competency, there are some difficulties the teachers face in the teaching and learning activity, such as: the understanding of GBA, and the mastery of Type of Text. The research finding of this study indicates that the implementation of GBA in the teaching of English in SMP Negeri 5 Sragen gives a good contribution to the improvement of the students’ language proficiency.